PERSEPSI MAHASISWI JURUSAN PENKESREK ANGKATAN 2016 FAKULTAS ILMU OLAHRAGA UNIVERSITAS NEGERI SURABAYA - ginting, satni; pudjijuniarto, pudjijuniarto pudjijuniarto (Jurnal Kesehatan Olahraga, 2019)
The problems in the study will certainly vary as well as the perceptions among the 2016 PENKESREK FIO Student.The purpose of this study was to obtain information about the perceptions of the 2016 FIO PENKESREK students towards the maseus profession at UNESA. This type of research is descriptive qualitative and direct data taken through research questionnaires. The population taken in this study were female students majoring in PENKESREK 2016 FIO UNESA who had taken the mass course in the February - June 2018 semester totaling 18 people. This research was conducted in the 2018/2019 school year, namely on the 7th and 11th of 2018. Data were collected through questionnaires and analyzed using percentages manually. In accordance with the results of data analysis, the results of the study were obtained from 18 female students who indicated that the perception of PENKESREK students in 2016 FIO UNESA was based on indicators namely female perception based on indicators of female students' views on maseus profession, perceptions of female students based on knowledge indicators negeri surabaya about sports massage, perceptions of female students based on attitude indicators of female students majoring in education in 2016 force of the state university of Surabaya sports science about sports massage and perceptions of female students based on experience indicators include student background and hobby of female students with a percentage value of the overall study which reached (sixty-five percent). From the four indicators, it can be concluded that the perceptions of 2016 UNESA FIO PENKESREK students to the maseus profession are good.Key Word: Perception, Student University, Maseus Professionals.